Importance and efficacy of health promotion by primary care nurses - Alanazi, Taghreed Ayed; Alanazi, Hind Ayed; Alanazi, Abeer Ayeed; Alharbi, Nawal Naseer; Alsumairi, Mashael Abdulhadi; Aldossari, Wejdan Hussein; Al Ruwili, Abeer Ruwayshid; Alanazi, Mashael Raja; Alwadai, Khalid Saad (International Journal Of Community Medicine And Public Health, 2022)
The core of many countries’ primary care strategies has been increasing community engagement in primary care, greater efforts in preventive illnesses and promoting health, and greater harmony and synergy of current services in accordance with the community’s needs. Primary care nurses have a lot of opportunity to provide strategies for health promotion and prevention, and prior research has revealed the multitude of functions that nurses can play, such as managing complex medical problems. Nurses employed in general practices have been observed to be effective in providing a number of preventative initiatives, including smoking cessation. It has been seen that though nurses who work in this environment are eager to counsel patients about physical exercise but have major deficiencies in their understanding of existing recommendations, suggesting a dearth of training preparation for such tasks. Very often, primary health care nurses’ ability to undertake health promotion is restricted by the general practice environment, their skillset, and general practitioners’ perspectives toward nurses’ participation in health promotion activities. Primary care nurses may be able to bridge the gap between societal expectations of this field and how patients view prevention in the context of general practice. Primary care nurses have a lot of room to grow in their ability to collaborate with other healthcare providers and work outside the confines of general practice settings. In primary care settings, nursing appears to be underused despite its potential to be working more successfully in HPP. The effectiveness of present primary health care changes depends on identifying and addressing the enablers and hurdles to health promotion and prevention among primary care nurses.